Reconceptualization of Empowerment Principles by Banking in Supporting Small and Medium Enterprises According to Law No. 20 of 2008 Concerning SMEs - Ukay Karyadi; Lutfi Trisandi Rizki (APPTHI, 2018)
In the economy, Small and Medium Enterprises (SMEs) are the business groups that have the largest number of business actors. In addition, this group has proven to be resistant to various kinds of shocks from the economic crisis. It is very important to strengthen the SME group that involves many parties because the SME sector contributes greatly to employment. The criteria for businesses included in SMEs have been regulated under the legal umbrella based on the law, especially Law No. 20 of 2008 concerning SMEs. This study aims to determine the role of banking in empowering SMEs by using the empowerment principle as stated in Law No. 20 of 2008 concerning SMEs. Law No. 20 of 2008 concerning SMEs provides a foundation and an important role for banks and financial institutions in funding and empowering SMEs. In accordance with the principle of empowerment, a broader effort is needed to foster a business climate by establishing laws and policies covering aspects of funding. From an empowerment perspective, banks indirectly play a role in driving the community's economy by channeling funds to the real sector in society. Further, the development of the SME sector will be able to absorb more workers, improve the welfare of the working community the workforce, reduce unemployment, and ultimately alleviate poverty. Abstrak Dalam perekonomian, Usaha Kecil dan Menengah (UKM) merupakan kelompok usaha yang memiliki jumlah pelaku usaha terbesar. Selain itu, kelompok ini terbukti tahan terhadap berbagai macam goncangan akibat krisis ekonomi. Penguatan kelompok UKM yang melibatkan banyak pihak ini sangat penting karena sektor UKM memberikan kontribusi besar dalam penyerapan tenaga kerja. Kriteria usaha yang termasuk dalam UKM telah diatur dalam payung hukum berdasarkan undang-undang, khususnya Undang-Undang Nomor 20 Tahun 2008 tentang UKM. Penelitian ini bertujuan untuk mengetahui peran perbankan dalam pemberdayaan UMKM dengan menggunakan prinsip pemberdayaan sebagaimana tertuang dalam UU No. 20 Tahun 2008 tentang UMKM. Undang-Undang Nomor 20 Tahun 2008 tentang UKM memberikan landasan dan peran penting bagi bank dan lembaga keuangan dalam pembiayaan dan pemberdayaan UKM. Sesuai dengan asas pemberdayaan, diperlukan upaya yang lebih luas untuk menumbuhkan iklim usaha dengan menetapkan peraturan perundang-undangan dan kebijakan yang mencakup aspek pendanaan. Dari sisi pemberdayaan, dengan menyalurkan dana ke sektor riil di masyarakat, secara tidak langsung bank berperan dalam menggerakkan perekonomian masyarakat. Selanjutnya, pengembangan sektor UKM akan mampu menyerap lebih banyak tenaga kerja, meningkatkan kesejahteraan masyarakat pekerja dalam angkatan kerja, mengurangi pengangguran dan pada akhirnya mengentaskan kemiskinan. Kata kunci: Rekonseptualisasi, Prinsip Pemberdayaan, UKM, Bank